Low-Level Laser-Aided Orthodontic Treatment of Periodontally Compromised Patients: A Randomized Controlled Trial - Sachin B. Mangalekar; Ipsita Jayanti; Anurag Tiwari; Shobhit Saxena; Abhijith Ajith; Arun Vashisht; Naina Pattnaik (Journal of Pharmacy and Bioallied Sciences)
Background: Periodontal disease can complicate orthodontic treatment, presenting challenges in maintaining both periodontal health and achieving desired orthodontic outcomes. Low-level laser therapy (LLLT) has emerged as a potential adjunctive treatment to enhance periodontal healing and facilitate orthodontic tooth movement. Materials and Methods: A randomized controlled trial was conducted with 60 periodontally compromised patients (mean age: 35 years). Participants were randomly assigned to either the experimental group, receiving LLLT in conjunction with standard orthodontic treatment, or the control group, receiving standard orthodontic treatment alone. The primary outcomes measured were changes in periodontal indices, tooth movement rate, and patient-reported pain levels. LLLT was applied at a wavelength of 810 nm with an energy density of 5 J/cm² for 10 min per session, twice weekly for 8 weeks. Results: The experimental group showed a significant improvement in periodontal indices, with a mean reduction in probing depth of 2.3 mm compared to 1.2 mm in the control group (P < 0.05). The rate of orthodontic tooth movement was faster in the LLLT group, with an average of 1.5 mm/month versus 1.0 mm/month in the control group (P < 0.01). Additionally, patient-reported pain levels were significantly lower in the LLLT group, with an average pain score reduction of 3.2 on a 10-point scale compared to 1.8 in the control group (P < 0.05). Conclusion: Low-level laser therapy significantly enhances periodontal health, accelerates tooth movement, and reduces pain in periodontally compromised patients undergoing orthodontic treatment.